The Need to Consider Relative Age Effects in Women's Talent Development Process. Issue 3 (June 2014) - Romann, Michael; Fuchslocher, Jörg
Relative age effects (RAEs) refer to age differences among athletes in the same selection year. This study analyzed birth date distributions of 301, 428 female athletes (aged 10–20 yr.) in Swiss Youth sports and the subgroup ( n = 1, 177) of the National Talent Development Program (TDP) in individual sports. Comparisons showed significant RAEs in the distribution of athletes' birth dates in alpine skiing, tennis, athletics, fencing, and snowboarding. Significant "reverse" RAEs with an overrepresentation of athletes at the end of the year were found in table tennis. In the TDP, significant RAEs were found in alpine skiing and tennis. No RAEs were detected in athletics. In table tennis, fencing, and snowboarding, "reverse" RAEs were found. Clearly, RAEs are complex and vary across individual sports for females.